On a new class of infinite groups - Ivko М. N.; Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The present paper is devoted to the study of properties of a new class of Φ-groups. The class of layer-finite groups is characterized with an accuracy to within this class.